The Cyclic Nature of Joni Mitchell's Court and Spark - Neimoyer, Susan (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2014)
Current scholarship recognizes several of Joni Mitchell’s albums as being cyclic, or based on a unifying concept. Court and Spark (1974), however, is not numbered among them, despite Mitchell’s having described it as “a discourse on romantic love.” Following the inference that this album may have been conceived as an extended, multi-movement work, this article examines both its textual and musical aspects, seeking unifying characteristics. The cyclic nature of the album is uncovered, showing it to be more unified from a musical perspective than a textual one. This approach is the opposite of Mitchell’s perceived norm, suggesting her compositional process may have been more sophisticated than is currently thought.